ANALISIS PENGARUH MOTIVASI, DISIPLIN KERJA DAN IKLIM ORGANISASI TERHADAP KINERJA PERANGKAT DESA DI KECAMATAN MANDAH KABUPATEN INDRAGIRI HILIR RIAU - jurnalmap map (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2022)
The purpose of this study is to describe the motivation, work discipline and organizational climate of their influence on the performance of village officials in the District of Mandah, Indragiri Hilir Regency. This research is a quantitative descriptive study with a total sample of 48 respondents. The results showed that motivation had a partial effect on the performance of village officials. Work discipline has a partial effect on the performance of village officials. F test results of motivation, work discipline and organizational climate simultaneously influence on the performance of village officials in the District of Mandah, Indragiri Hilir Regency. The results of the coefficient of determination test show that the influence of motivation, work discipline and organizational climate on the performance of village officials in Mandah Subdistrict, Indragiri Hilir Regency is 95.5%, while the remaining 4.5% can be explained by other variables outside of the research variables.